2001
DOI: 10.3168/jds.s0022-0302(01)74510-9
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Acetone in Cow Milk by Fourier Transform Infrared Spectroscopy for the Detection of Subclinical Ketosis

Abstract: Fourier transform infrared analysis (FTIR) was used in combination with partial least squares regression (PLS) to predict the concentration of acetone in milk. FTIR spectra were compared with results of a gas-chromatographic head space method. Principal component analysis of whole spectra (3000 to 1000 cm(-1)) suggested to reduce the spectrum of analysis for acetone to 1450 to 1200 cm(-1). A second derivative was applied to the spectra to remove baseline effects and further enhance the spectral features. Full … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
64
0
3

Year Published

2010
2010
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 10 publications
2
64
0
3
Order By: Relevance
“…Its potential has also been demonstrated to predict coagulation properties of bovine milk (Dal Zotto et al, 2008;De Marchi et al, 2009b), detail milk protein composition (De Marchi et al, 2009a) and -E-mail: mauro.penasa@unipd.it acetone content for the detection of subclinical ketosis (Heuer et al, 2001). Soyeurt et al (2006) and Rutten et al (2009) demonstrated the accuracy of the prediction of FA composition using MIR, but only for the most representative FA.…”
Section: Introductionmentioning
confidence: 99%
“…Its potential has also been demonstrated to predict coagulation properties of bovine milk (Dal Zotto et al, 2008;De Marchi et al, 2009b), detail milk protein composition (De Marchi et al, 2009a) and -E-mail: mauro.penasa@unipd.it acetone content for the detection of subclinical ketosis (Heuer et al, 2001). Soyeurt et al (2006) and Rutten et al (2009) demonstrated the accuracy of the prediction of FA composition using MIR, but only for the most representative FA.…”
Section: Introductionmentioning
confidence: 99%
“…Hansen (1999) cross-validated FTIR prediction of milk acetone with reference measurement of acetone in milk and concluded that the model could differentiate "possibly ketotic" from healthy cows with no false negatives and 27% false positives. In addition, Heuer et al (2001) developed a FTIR prediction model for milk acetone to identify subclinical ketotic cows, which resulted in positive predictive values of >76% and negative predictive values of >98% in a population with prevalence of subclinical ketosis of 10 to 30%. It can be hypothesized that FTIR predictions of BHBA and acetone in milk could be valuable in screening of dairy cows for hyperketonemia.…”
mentioning
confidence: 99%
“…Prevention can be carried out by various forms of nutrition modifi cations in early lactation such as fast energy or hepatoprotective matters supplementation into cow feeding ration (Emery et al, 1964;Miettinen, 1995;Gasteiner, 2003;Tedesco et al, 2004;Coskun et al, 2012). In this sense blood, urine and milk indicators and their thresholds and interpretations are important (Heuer et al, 2000;Enjalbert et al, 2001;de Roos et al, 2007;Hanuš et al, 2001Van der Dri et al, 2012). Real time analyses of main milk components are attended in milking parlours today.…”
Section: −1mentioning
confidence: 99%
“…The others are linked with sure reduction of body condition score in postpartum period (Gasteiner, 2000;Beran et al, 2012). However, most of them are described by high blood, urine or milk AC (ketone) level (Andersson, 1984;Hansen, 1999;Heuer et al, 2000;Enjalbert et al, 2001;Hanuš et al, 2001de Roos et al, 2007;Van der Dri et al, 2012), sometimes with a relevant note about clinical signs. The results of this cross validation are comparable with research results of other authors as follows: Duffi eld et al, 1997, F/CP 1.33;Ziebell, 1995 andGeishauser et al, 1997, F/CP 1.4;Van Knegsel et al, 2010, F/CP 1.5;Siebert and Pallauf, 2010, F/CP 1.33 and 1.5; Manzenreiter et al, 2013, F/CP 1.33;Steen et al, 1996, F/L 1.0;Reist et al, 2002, F/L 1.0;Manzenreiter et al, 2013, F/L 0.9. This reciprocal estimation of cut-off limits by cross validation has confi rmed following general facts: -milk component AC and component quotients F/CP and F/L as ketosis indicators are in usable and good relationships in early lactation for diagnostical possibilities in case of SK; -confi rmation of ketosis milk quotient thresholds by cross calculation shows good agreement; -simultaneously combined use of all milk indicators could be diagnostically advantageous because of cross validation results.…”
Section: Reciprocal Estimation Of F/cp and F/l Threshold By Cross Calmentioning
confidence: 99%